Formation of pressurizable hydrogel-based vascular tissue models by selective gelation in composite PDMS channels. Issue 16 (19th March 2019) - Fukushi, Mayu; Kinoshita, Keita; Yamada, Masumi; Yajima, Yuya; Utoh, Rie; Seki, Minoru
Abstract : A new approach for the preparation of vascular tissue models in PDMS-based composite channel structures embedded with barium salt powders. Abstract : Vascular tissue models created in vitro are of great utility in the biomedical research field, but versatile, facile strategies are still under development. In this study, we proposed a new approach to prepare vascular tissue models in PDMS-based composite channel structures embedded with barium salt powders. When a cell-containing hydrogel precursor solution was continuously pumped in the channel, the precursor solution in the vicinity of the channel wall was selectively gelled because of the barium ions as the gelation agent supplied to the flow. Based on this concept, we were able to prepare vascular tissue models, with diameters of 1–2 mm and with tunable morphologies, composed of smooth muscle cells in the hydrogel matrix and endothelial cells on the lumen. Perfusion culture was successfully performed under a pressurized condition of ∼120 mmHg. The presented platform is potentially useful for creating vascular tissue models that reproduce the physical and morphological characteristics similar to those of vascular tissues in vivo .